MODL-25. ANALYSIS OF TUMOR CELL HETEROGENEITY IN A HUMAN NEURAL PROGENITOR-BASED MODEL OF GLIOBLASTOMA REVEALS NEURODEVELOPMENTAL PROGRAMS AND CYTOSKELETAL DYNAMICS. (14th November 2022) - DeSouza, Patrick; Qu, Xuan; Ishahak, Matthew; McCornack, Colin; Annamalai, Devi; Batista, Luis; Wang, Ting; Maher, Christopher; Millman, Jeffrey; Kim, Albert
Abstract: Glioblastoma (GBM) is the most common primary malignant neoplasm with poor survival despite treatment. Developing effective therapies remains challenging due to intratumoral heterogeneity, which drives therapeutic resistance and recurrence. To understand how genetic events alter the epigenome to enhance clonal fitness, we developed an isogenic human neural progenitor cell (NPC)-based model of the proneural (PRO) GBM subtype. We introduced TERT promoter (TERTp) C228T and gain-of-function TP53 R248Q mutations in H1 human embryonic stem cells. Wildtype (WT) cells, single TERTp, and double TERTp/TP53 mutants underwent differentiation to NPCs. Lentiviral transduction of double mutants with PDGFRA D842V resulted in triple mutant PRO NPCs. Bulk and single cell transcriptomics of our model system revealed hundreds of gene expression changes with increased mesoderm and human GBM mesenchymal (MES) subtype signatures in single TERTp and double TERTp/TP53 mutants, versus WT cells. TERTp mutation increased telomerase expression and activity, conferring proliferative advantage and immortalization in NPCs and astrocytes. Additionally, TERT expression was further increased in TERTp/TP53 mutants. Surprisingly, triple mutant PRO NPCs, versus WT, displayed < 100 differentially expressed genes, associated with neurodevelopmental and dynamic cytoskeletal processes. Evolution analyses using gene counts signature and splicing dynamics revealed a developmental trajectory model from WT to additive mutants to PRO NPCs. Only triple mutant PRO NPCs formed tumors after intracranial injection in athymic nude mice, with mean survival of 100 days. Tumors presented histopathological features of GBM, and single cell transcriptomic analyses revealed evolution from immune-interacting to both neural progenitor- and neuronal-like subpopulations, with similar cell cycling signatures. Transcription factor genes related to WNT signaling and lineage commitment as well as glial and neuronal cytoskeletal genes exhibited epigenetic selection in vivo, signatures also observed in PRO NPCs in vitro . Our model thus provides opportunity for dissection of epigenetic and functional mechanisms underlying serial mutations during PRO tumor evolution.